2022
DOI: 10.1021/acsomega.1c07132
|View full text |Cite
|
Sign up to set email alerts
|

Photo-on-Demand Phosgenation Reactions with Chloroform for Selective Syntheses of N-Substituted Ureas and Isocyanates

Abstract: Two new reaction processes involving the in situ oxidative photochemical conversion of CHCl 3 to COCl 2 allowed selective syntheses of N-substituted ureas and isocyanates from amines. (I) A CHCl 3 solution containing an amine and an organic base under O 2 bubbling provided the urea derivative under exposure to UV light generated from a low-pressure mercury lamp at 20−40 °C. (II) A two-step reaction involving the oxidative photodecomposition of CHCl 3 at lower temperatures and subsequent sequential injections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In support of this proposed mechanism, commercially available l -Phe·HCl was found to provide the corresponding NCA in 70% yield (Table , entry 1I). Thus, the reaction takes a longer time at higher temperature compared with other phosgenation reactions reported previously. For safe handling of the reaction, the generated amount of COCl 2 should be regulated by ON–OFF cycles and/or intensity of the photo-irradiation, and the vaporized COCl 2 and generated HCl must be trapped with alcohol and alkaline water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this proposed mechanism, commercially available l -Phe·HCl was found to provide the corresponding NCA in 70% yield (Table , entry 1I). Thus, the reaction takes a longer time at higher temperature compared with other phosgenation reactions reported previously. For safe handling of the reaction, the generated amount of COCl 2 should be regulated by ON–OFF cycles and/or intensity of the photo-irradiation, and the vaporized COCl 2 and generated HCl must be trapped with alcohol and alkaline water.…”
Section: Resultsmentioning
confidence: 99%
“…Contrarily, other chlorocarbons such as CCl 4 and CH 2 Cl 2 produced less amounts of COCl 2 through similar photochemical reactions. The reaction with CHCl 3 could be applied to a variety of in situ phosgenation reactions like with BTC. Compared with BTC, CHCl 3 is an inexpensive and more abundant compound capable of being used as a solvent. Further, the reaction allows photo-on-demand control of phosgenation reactions without using the chemical additives.…”
Section: Introductionmentioning
confidence: 99%
“…We expect that it will contribute to the sustainable organic synthesis capable of reducing chemical waste and CO 2 emissions and will be used mainly in industry . For the academic purpose, however, it is preferable to use the in situ batch photo-on-demand phosgenation reactions reported mainly by our group for safety reasons. …”
Section: Discussionmentioning
confidence: 99%
“…As an alternative on-demand method to generate COCl 2 , we previously reported oxidative photochemical conversion of CHCl 3 to COCl 2 upon exposure to UV light with a batch reaction system. Although the reaction proceeds without chemical reagents, its efficiency with respect to the amount of CHCl 3 has not been clarified quantitatively. Herein, we studied a novel flow photochemical oxidation of CHCl 3 under precise control of the flow rates of CHCl 3 and O 2 and found that the reaction occurred efficiently in the gas phase in a short time to give COCl 2 in over 96% yield (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…This background motivated us to develop direct in situ photo-on-demand synthesis of NTCAs from TCE solutions containing primary amines (Scheme , reaction IV). We have intensively studied photo-on-demand phosgenation reactions with chloroform (CHCl 3 ), which allows in situ photochemical conversion of CHCl 3 to COCl 2 even in the presence of reaction substrates and organic bases capable of absorbing UV light. We thus expected that photochemical conversion of TCE to TCAC would occur similarly in the presence of amine substrates, and the generated TCAC would then immediately react in situ with the amine without an organic base to afford NTCA.…”
Section: Introductionmentioning
confidence: 99%